2007
DOI: 10.1099/jmm.0.46790-0
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based identification and strain typing of Pichia anomala using the ribosomal intergenic spacer region IGS1

Abstract: Frequent outbreaks of Pichia anomala fungaemia in paediatric patients have warranted the development of a rapid identification system for this organism. This study describes a specific PCR-based method targeting the rRNA gene intergenic spacer region 1 (IGS1) for rapid identification of Pichia anomala isolates and characterization at the strain level. These methods of species identification and strain typing were used on 106 isolates of Pichia anomala (77 from a previously described outbreak and 29 isolated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In most cases, sequences of the internal transcribed spacer (ITS) regions have, to date, not yielded sufficient variation to enable strain differentiation . In contrast, sequences of the intergenic spacer (IGS) have been used to differentiate pathogenic and non-pathogenic strains (Bhardwaj et al 2007). Kalkanci et al (2010) found identical banding patterns for clinical C. pelliculosa isolates when using different random amplified polymorphic DNA (RAPD) primers.…”
Section: Strain Diversitymentioning
confidence: 98%
“…In most cases, sequences of the internal transcribed spacer (ITS) regions have, to date, not yielded sufficient variation to enable strain differentiation . In contrast, sequences of the intergenic spacer (IGS) have been used to differentiate pathogenic and non-pathogenic strains (Bhardwaj et al 2007). Kalkanci et al (2010) found identical banding patterns for clinical C. pelliculosa isolates when using different random amplified polymorphic DNA (RAPD) primers.…”
Section: Strain Diversitymentioning
confidence: 98%
“…lactis from Kluyveromyces marxianus (Nguyen et al , 2000b) or from its closest wild relatives (Naumova et al , 2004). The IGS1 (=NTS1) proved useful for identification and typing of Pichia anomala strains (Sutar et al , 2004; Bhardwaj et al , 2007) and of Trichosporon species (Sugita et al , 2002). The entire IGS region has also been used, after amplification with primers selected inside the RDN25 and RDN18 conserved regions, to identify several basidiomycetous yeasts (Fell & Blatt, 1999; Diaz & Fell, 2000; Diaz et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…anomala is sometimes identified from cultures, but peripheral laboratories frequently fail to identify this organism because of the rarity of infection and lack of expertise in its identification [15]. In this case, DNA sequence analysis of fungal rRNA was helpful in identifying P. anomala.…”
mentioning
confidence: 88%